Method Development, Validation and Stability Study of Irbesartan in Bulk and Pharmaceutical Dosage Form by UV-Spectrophotometric Method - Pradhan, Kishanta Kumar (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT A simple, precise, accurate and stability indicating UV-method have been developed and validated for estimation of Irbesartan. Many experiments were conducted by taking combination of drugs & also by single drug but no suitable validation with stability studies were reported. Irbesartan has the absorbance maxima at 246nm.Method A involves method development and validation, showed sharp peak at 246nm.Method B involves forced degradation study. All the methods utilize methanol as solvent. Linearity for the detector response was observed in the concentration range of 5-45 Âµg/ml. Validation experiments were performed to demonstrate System suitability, Specificity, Precision, Linearity, Accuracy Precision, robustness, ruggedness. Furthermore stability studies of Irbesartan were carried out under acidic, alkali, neutral, oxidation &photolytic degradation as per stability indicating assay methods. The results of analysis have been validated and recovery studies were carried out by adding specific drug amount (80%, 100%, and 120%) and shows recovery studies in the range (99.335-100.583) %. The proposed method can be successfully applied for method development, validation and stability study of Irbesartan.